DEKADENSI MORAL GENERASI MUDA AMERIKA TAHUN 1920-AN YANG TERCERMIN DALAM NOVEL THE BEAUTIFUL DAN DAMNED KARYA FITZGERALD - Rizki Februansyah; Daryanto Daryanto (University of Muhammadiyah Purwokerto, 2007)
This research discusses about moral deviations of Ameican youth toward moral and ethic code—Puritan that had been deeply rooted in American life for hundreds of years.The purpose of the reasearch is to elaborate the impact of socio-cultural changes in American during twenties in tune with the process of modernization after World war I on American society paticularly the younger generation.By applying structural and sociological approach, the writer analyzes the impact of socio-cultural changes toward the youth’s morality through the attitude of characters in the novel.This research shows that the socio-cultural changes the youth’s morality.The youngergeneration developed new values in keeping with the prosperity of the country. They oopenly revealed their impatience in such deviant ways. They actualized their new freedom by drinking liqour, doing free sex, and living hedonistic life style